Situational and Dispositional Factors that Predict Motivation: a Multilevel Study - Pineda Espejel, Heriberto Antonio; López Walle, Jeanette M.; Tomás, Inés (2017)
Abstract. This study aimed to test a multilevel mediation model which examined the relationship between the perceived motivational climate created by coaches at team level and motivational regulations towards sport at individual level, as mediated by individual goal orientations. 211 university athletes from 20 teams training in different types of sport completed a battery of instruments that measured the variables included in the model. The statistics significance level was .05. Results of the multilevel mediation model revealed that the task-involving climate at team level positively predicted individual task orientation (γ01 = .77, p < .001) and autonomous motivation for sport practice (γ01 = .68, p = .03). Task orientation positively predicts the autonomous motivation (γ10 =.51, p < .01), and inversely the non motivation (γ10 = –.76, p < .001). Also task orientation partially mediated the relationship between task-involving climate and autonomous motivation (b1b2 = .39; 95% CI = [.11, .68]; τ = .68, p < .05), and fully mediated the relationship between task-involving climate and amotivation (b1b2 = –.58; 95% CI = [–.92, –.25]; τ = –.62, p >.05). The results are in line with previous research that have focused in the study of motivational climate at individual level, but the present study make a novel contribution by providing the perspective of a multilevel mediation model and thereby clarifying the phenomenon at team level.